JOKOWI DI DEPAN DAN BELAKANG PANGGUNG POLITIK - Leovina Prinanda Putri; Muhammad Ahsan Ridhoi; Novita Anggraini (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2021)
Indonesia reached a turning point in its implementation of eradicating corruption after the fall of the Soeharto regime in 1998. Corruption then became a sexy issue that became the commitment of politicians and public officials. Jokowi appeared and became a favorite media. In the 2014 presidential election campaign, Jokowi carried 9 Nawa Cita promises, on the 4th point containing: